A ’Safe Space’ for Disagreement? : An Experiment on the Effect of Social Media Cross-Cutting Exposure on Internal Political Efficacy - Bene, Márton; Patkós, Veronika (Central European Journal of Communication, 2026)
We investigate whether cross-cutting and mixed exposure to political information on social media is associated with users’ internal political efficacy using an online survey experiment. Existing research has demonstrated several benefits of cross-cutting exposure, but they have also shown its dark side. Mutz (2006) found that political ambivalence is significantly associated with cross-cutting talk as disagreement makes people more uncertain about their political views. However, it has been not investigated if cross-cutting exposure makes people more uncertain about their own political capacities to understand politics and meaningfully participate within it. Our research question is whether this detrimental effect on internal political efficacy can be detected on social media context. The findings show that participants’ internal political efficacy is not significantly shaped by the type of exposure. Consequently, cross-cutting exposure on social media can be seen a ‘safe space’ for political disagreement where the ‘dark side’ of cross-cutting exposure cannot prevail.